The impact of quarantine strategies on malware dynamics in a network with heterogeneous immunity - Al-Tuwairqi, Salma M.; Bahashwan, Walaa S. (Mathematical Modelling and Analysis, 2022)
In this paper, we investigate the influence of two types of isolation on malware propagation within a computer network. Model 1 proposes the network quarantine strategy, where infected computers are fully disconnected from the network. As for model 2, the control strategy is the anti-virus software quarantine, where infected files in a computer are contained in an isolation folder. Both models consider the aspect of heterogeneous immunity, that is, weak and strong immunization of computers in a network. Analytical examinations produced a virus-free equilibrium and an endemic equilibrium for each model. It has been observed that the quarantine reproduction number Rq plays an essential role in the existence and stability of the equilibrium points. Furthermore, numerical simulations are accomplished to substantiate the qualitative results. Finally, a sensitivity analysis is executed to specify the dominant parameters on Rq. It is found that the performance of network quarantine is better than anti-virus software quarantine in controlling malware propagation.